Carta de Ferdinand R. Cestero a Roberto H. Todd - Cestero, Ferdinand R.; Todd, Roberto H. (My University, 1942)
Agradecimiento por el homenaje a Cestero.
Keywords: Cestero, Ferdinand R.--Correspondencia.; Cestero, Ferdinand R.--Correspondence.